Glebus Sainciuc -an active ﬁgure in the cultural life of the country (Confluenţe Bibliologice, 2019)
The article describes sequences from the life and activity of the Bessarabian plastic artist Glebus Sainciuc (1919-2012), portraitist, known especially for his collection of papier maché masks, which he presented himself, whose creation occupies an important place in development of ﬁne arts in the Republic of Moldova.
Keywords: Glebus Sainciuc (1919 - 2012); Bessarabian painters; collection of the USARB Scientiﬁc Library; anniversary exhibition